Can the nano level electrodynamics explain the very early diagnosis of diabetic nephropathy in type-2 diabetes patients? - Nieto Chaupis, Huber (2017)
By assuming that the dipole moment of glucose might be high enough to cancel the negative charges of glomerulus, we estimate the efficiency of the sensing of negatively charged albumin proteins as well as the Tamm-Horsfall's proteins (THP). The knowledge of the charge distributions in time of both albumin and THP would denote an advantage since the efficient sensing of albumin might be perceived as a very early diagnosis of the diabetic kidney disease (DKD). The proposed mathematical methodology based on classical electrodynamics has assumed that the product of charge densities coming from the interaction between glomerulus and glucose ρGM × ρGL might be a possible signal of albumin passing through from the renal glomerulus through the external convoluted tubule. According to simulations the sensing of albumin might be of order of 72% which means that the THP is a strong source of noise and mimic well to signal.